Understanding Learning Concepts in Grade 10 Students During Classroom Practices: Case Study BBC Senior High School in Medan - Bunga Santi Br. Ritonga; Cindy Syahputri; Elina Rewinata Pangaribuan; M. Ihsan Maulana (SAKAGURU: Journal of Pedagogy and Creative Teacher, 2026)
Students’ conceptions of learning influence how they interpret academic demands, regulate motivation, select learning strategies, and evaluate educational success; however, limited qualitative evidence explains how these dimensions are interconnected among Indonesian senior high school students. This study aimed to explore Grade 10 students’ understanding of learning, identify the internal and external factors influencing their learning, examine the strategies they employed, and determine the indicators through which they evaluated learning success. A descriptive qualitative case-study design was employed at SMA BBC Medan, involving six purposively selected Grade 10 students representing different genders and levels of academic achievement. Data were collected through individual semi-structured interviews guided by eight open-ended questions and analyzed using the interactive model of data condensation, data display, and conclusion drawing. Member checking and cross-participant comparison were conducted to strengthen the credibility of the findings. The results revealed that students predominantly conceptualized learning as the acquisition of knowledge and experience, while affective, behavioral, and psychomotor dimensions were less frequently recognized. Motivation and personal willingness emerged as the most influential internal factors, whereas family support, conducive learning environments, and engaging teaching practices constituted important external influences. Students relied mainly on conventional strategies, including reading, note-taking, discussion, repeated practice, scheduling, and reviewing materials, but rarely reported metacognitive practices such as goal setting, self-monitoring, reflection, or strategy evaluation. Learning success was primarily associated with improved grades, although some students also identified conceptual understanding, problem-solving ability, confidence, motivation, and behavioral change. The study concludes that students possess a foundational but transitional understanding of learning that remains strongly cognitive, instrumental, and achievement-oriented. These findings imply that teachers and school counselors should collaboratively develop learning guidance that broadens students’ conceptions of learning, strengthens autonomous motivation, and explicitly cultivates metacognitive and self-regulated learning skills.